2009
DOI: 10.1002/jat.1421
|View full text |Cite
|
Sign up to set email alerts
|

Improved cell sensitivity and longevity in a rapid impedance‐based toxicity sensor

Abstract: A number of toxicity sensors for testing field water using a range of eukaryotic cell types have been proposed, but it has been difficult to identify sensors with both appropriate sensitivity to toxicants and the potential for long-term viability. Assessment of bovine pulmonary artery endothelial cell (BPAEC) monolayer electrical impedance with electric cell-substrate impedance sensing (ECIS) showed promise in a previous systematic evaluation of toxicity sensor technologies. The goal of the study reported here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 23 publications
0
30
0
1
Order By: Relevance
“…If 6°C storage is not available, then cell lines with different optimal storage temperatures could be utilized and tailored for the testing environment. It has been shown that fish and reptilian cell lines have toxicant sensitivities comparable to mammalian cell lines (Brennan et al, 2012;Curtis et al, 2009a); indicating that a wide variety of vertebrate cells could be used as accurate predictors of human toxicity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…If 6°C storage is not available, then cell lines with different optimal storage temperatures could be utilized and tailored for the testing environment. It has been shown that fish and reptilian cell lines have toxicant sensitivities comparable to mammalian cell lines (Brennan et al, 2012;Curtis et al, 2009a); indicating that a wide variety of vertebrate cells could be used as accurate predictors of human toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Impedance measurements of cells on the open well chips and fluidic biochips were monitored using the ECIS 1600 analyzer (Applied BioPhysics, Troy, NY) as previously described by Curtis et al (2009a). Table 2 summarizes the cells performance in open well ECIS chips.…”
Section: Impedance Measurement With Ecismentioning
confidence: 99%
See 1 more Smart Citation
“…Cellular impedance has been shown to be a sensitive indicator of cell viability and cytotoxicity (Giaever and Keese, 1993;Curtis et al, 2009a;Keese et al, 1998;Xing et al, 2005Xing et al, , 2006. Other investigators have found excellent correlation between cellular impedance and other toxicity endpoints such as tetrazolium dye and neutral red uptake assays (Xing et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…One of the main reasons for the recent success is the development of cellbased sensor systems which can be used in field applications [21]. In this context, Electrical cell impedance spectroscopy [22] has been demonstrated to be feasible to monitor various aquatic toxicants including heavy metals and industrial pollutants [23]. Cr(VI) detection using cell-based impedance sensors was already performed before, using the Real-Time Cell Electronic Sensor [24].…”
Section: Introductionmentioning
confidence: 99%